2018
DOI: 10.1159/000492001
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Oxytocin Concentration in Pre- and Postmenopausal Women: Its Relationship with Obesity, Body Composition and Metabolic Variables

Abstract: Objective: To investigate the relationship between oxytocin, menopause and obesity. Methods: A cross-sectional analysis on 56 obese (OB; 28 premenopausal) and 53 normal-weight women (NW; 27 premenopausal) was performed by measurement of oxytocin, leptin, adiponectin, gonadotropins, sex steroids, glucose, and lipid homeostasis as well as DXA assessment of fat mass (%FM) and fat-free mass (FFM). Results: Women from NW and OB groups were comparable for age but differed in anthropometric measures. In our cohorts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 47 publications
2
23
1
Order By: Relevance
“…There is also evidence for higher peripheral OXT levels in individuals with excess energy stores, including overweight/obese women and men . However, in a number of studies of obese adults with a high prevalence of type 2 diabetes or insulin resistance and children with insulin resistance, OXT levels were low; this may be directly related to impaired glucose homeostasis as individuals with type 1 or type 2 diabetes have low OXT levels . Some studies in individuals with type 2 diabetes or insulin resistance and overweight/obesity have found that lower OXT levels are associated with increased features of metabolic syndrome .…”
Section: Endogenous Oxytocin Levels and Relationship To Markers Of Enmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence for higher peripheral OXT levels in individuals with excess energy stores, including overweight/obese women and men . However, in a number of studies of obese adults with a high prevalence of type 2 diabetes or insulin resistance and children with insulin resistance, OXT levels were low; this may be directly related to impaired glucose homeostasis as individuals with type 1 or type 2 diabetes have low OXT levels . Some studies in individuals with type 2 diabetes or insulin resistance and overweight/obesity have found that lower OXT levels are associated with increased features of metabolic syndrome .…”
Section: Endogenous Oxytocin Levels and Relationship To Markers Of Enmentioning
confidence: 99%
“…However, in a number of studies of obese adults with a high prevalence of type 2 diabetes or insulin resistance and children with insulin resistance, OXT levels were low; this may be directly related to impaired glucose homeostasis as individuals with type 1 or type 2 diabetes have low OXT levels . Some studies in individuals with type 2 diabetes or insulin resistance and overweight/obesity have found that lower OXT levels are associated with increased features of metabolic syndrome . However, one study of older men (mean weight 80 kg) (a minority of whom had type 2 diabetes) found that higher OXT levels were associated with greater weight and metabolic syndrome, and another of men and women across a wide spectrum of weights with insulin resistance in those with obesity reported higher OXT levels were associated with greater body mass index and insulin resistance (homeostatic model assessment of insulin resistance [HOMA‐IR]) .…”
Section: Endogenous Oxytocin Levels and Relationship To Markers Of Enmentioning
confidence: 99%
“…This result was in agreement with some previous reports. However, most of the related studies were done on postmenopausal women or women after ovariectomy [14,24]. Oxytocin is an anorexigenic neuropeptide that controls metabolic homeostasis mainly via regulating food intake and energy expenditure [25].…”
Section: Discussionmentioning
confidence: 99%
“…Oxytocin, a hypothalamic hormone that enters the peripheral circulation through the posterior pituitary, regulates a range of physiological processes, including reducing caloric intake, increasing energy expenditure, improving fat metabolism, and maintaining glucose homeostasis and insulin sensitivity [11][12][13]. Some studies have confirmed the association of plasma oxytocin with obesity, and oxytocin may play an important role in control of body weight in women [14]. Decreased oxytocin concentration is directly correlated with hypertension, dyslipidaemia, insulin resistance, and type 2 diabetes mellitus [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Although these intervention studies showed bene cial effects of OXT on T2DM-related metabolic pro les, how T2DM may affect endogenous OXT levels is still poorly understood. While previous studies in young to middle-aged adults have found an association between lower OXT levels and T2DM [6][7][8][9][10][11], others have reported con icting ndings with higher levels of OXT in metabolic disorders [12][13][14]. Furthermore, most studies investigating the association between OXT and T2DM are small-sized and stem from sex-speci c young populations.…”
Section: Introductionmentioning
confidence: 98%